Peningkatan Penalaran Dan Komunikasi Matematika Dalam Memecahkan Masalah Melalui Strategi Think-Talk-Write (PTK Pembelajaran Matematika Kelas VIII B Semester Genap SMP Negeri 2 Colomadu Karanganyar Tahun Ajaran 2012/2013) - Ulfah, Yulia, Prof. Dr. Budi Murtiyasa, M.Kom (2013)
This research has purpose to improve students' reasoning and mathematics communication of VIII B grade, SMP Negeri 2 Colomadu in problem solving by using Think-Talk-Write Strategy on the circle. Type of research is a classroom action research. The subject of this research the researcher as a teacher that provides classroom actions research and the actions receiver are the students of class VII B who are amount 31 students. Technique of collecting data are observation, record field, documentation and test methods. The approach of the research is descriptive qualitative by using groove method that is analyzed from action learning implemented and developed during the learning process. The results of the research showed an increasing in mathematics reasoning and communication. The findings of the research show: 1) the students are able to present a written statement to the math and drawing 90.32%, 2) the students are able to develop a proof of the validity of the solution 90.32%, 3) the students are able to perform mathematics manipulations 90.32%, 4) the students able to draw conclusions from statements 77.42%, 5) the students able to use mathematics language and symbols 80.64%, 6) the students listen to and discuss mathematics 83.88%, 7) the students are able to read comprehension 90.32%, 8) mathematics students written or oral presentations 70.97%. This research has conclusion that is by using Think-Talk-Write Strategy can improve students' mathematics reasoning and communication in problems solving.